Dried of Poultry Waste Urea-Molasses Block (dpw-umb) as Potential for Feed Supplementation - Danung Nur Adli; Osfar Sjofjan; Mashudi Mashudi (Jurnal Agripet, 2017)
ABSTRACT.The research purpose was to determine the nutrient content of dried poultry waste molasses block (DPW-UMB). The use of dried poultry waste in the manufacture of the urea-molasses block was as a substitute of urea and could improve the value added in dry season. The treatments used for research were T1 (15% manure layer chicken and 25% molasses), T2 (10% manure layer chicken and 30% molasses), and T3 (20% manure layer chicken and 30% molasses). Chemical analysis: the dried of poultry waste were analyzed for dry matter, crude protein, crude fibre, ash, fat, and gross energy. The statistical formulation diet composed with Microsoft Excel Ver. 2016. The results showed that the 20% manure layer chicken and 30% molasses (T3) were better than T2 and T1 on nutrient content with 92.04% Dry Matter (DM), 13.34% Crude Protein (CP), 13.39% Crude Fiber (CF), 37.16% ash, 3.44% fat, but low in Gross Energy (GE) (2631.63 kcal/kg). It could be concluded that dpw-umb T3 were dried of poultry waste contained sufficient levels of gross energy, crude protein, crude fibre, ash, and fat it could be used as feedstuff for ruminants for supplementation with the required nutrients.(Kotoran Ayam Molasses (Kamblok) Sebagai Potensi Supplementasi Pakan)ABSTRAK. Tujuan penelitian ini bertujuan untuk mengkaji kandungan nutrisi dari Kotoran Ayam Molasses Blok (KAMBLOK) dengan analisis proksimat. Sebagai bahan pengganti urea dengan kotoran ayam kering dalam pembuatan urea molasses blok dan meningkatkan nilai tambah dalam suplementasi Kotoran Ayam Molasses Blok (KAMBLOK) pada musim kemarau. Perlakuan yang digunakan pada penelitian ini adalah Kotoran Ayam Molasses Blok (KAMBLOK) dengan T1 (Kotoran Ayam Petelur 15% dan Molasses 25%), T2 (Kotoran Ayam Petelur 10% dan Molasses 30%), T3 (Kotoran Ayam Petelur 20% dan Molasses 30%). Analisis kandungan nutrisi yang dilakukan adalah bahan kering, protein kasar, serat kasar, abu, lemak, dan gross energi. Analisis statistik menggunakan Microsoft excel versi 2016. Hasil Penelitian menunjukan Kotoran Ayam Molasses Blok (KAMBLOK) T3 lebih baik dari T2 dan T1 pada bahan kering (BK) 92, 04%, protein kasar (PK) 13,34%, serat kasar (SK) 13,39%, abu 37,16%, lemak 3,44% tetapi rendah dalam gross energi (GE) adalah 2.631,63 kal/kg. Kesimpulan dari penelitian ini adalah kotoran ayam mengandung beberapa kandungan yaitu protein kasar, gross energy, serat kasar, abu, dan lemak yang bisa digunakan sebagai pakan potensial untuk supplementasi.